FAKTOR – FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR - Merna Surjadi; Sarton Sinambela (Universitas Bunda Mulia, 2017)
Objectives of the research are to examine and analyze the impact of the profitability, size dan liquidity to capital structure of the manufacturing firm listed in Indonesia Stock Exchamge. Samples are taken by using purposive sampling method and research has been done on 105 observations. The result show that profitability and size do not have significant impact on firm capital structure. On the other hand, liquidity has significant impact on capital structure. The next research is suggested to be done by different sectors of the firm and use more variable independent in a longer period of time to get a more comprehensive result.Keywords: capital structure, profitability, size, liquidity